The Persona Analysis of the Clown Persona in Osamu Dazai’s A Shameful Life - Anwar Willy Andhika; Prayudias Margawati (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2025)
Persona is one of Jung's archetypes, representing the mask or our other personality we make when we appear in front of people. The existence of personas is added to many forms of literature nowadays, especially in the character, which makes the story more complicated and enjoyable for the reader. Personas are given deep characteristics about the character's traits and psychological development. The novel "Shameful Life," also known as "No Longer Human," was written by Dazai Osamu and tells the life story of a man who lives as a clown to conceal his true nature from society. However, the clown persona that he is proud of and wears in his life becomes his prison for eternity. The qualitative research will be the main foundation of the paper’s method, which will be filled with a combination of data processing and theory. The method has succeeded in giving a detailed description of the Clown person and its cause and effect. The clown persona is a persona that is possessed and created by the main character using the reference of a clown. The main character believes that, if he could always use a clown persona and entertain people, he would be accepted by the human society, but those beliefs will be crushed by his own persona.